(3GdJMOjGJ GdJj JhGLg efXeGJ GdCYeGd GdeYGUQI (B:s (3GdCReI GdeGdjI hGdYGdejI hGdCaGb GdeSJbHdjI (B/s - (3GdbQjhJj, eMeOs; (3GdYHGOj, SejQs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2011)
(3efgL GdOYhI GdGSdGejI aj JCUjd CNdGbjGJ GdGeGd h GdeSDhdjI GdGLJeGYjI , GdaSGO GdGOGQj h GdTaGajI , GOGQI GdJZjjQ h GdJWhjQ GdGOGQj aj efXeGJ GdGYeGd , OhQ GdTaGajI aj GdMO ef GdMO ef GdaSGO GdGOGQj , GKQ GdbjGOI GdJMhjdjI aj GdhdGA fMh GdJZjjQ , eOi eTGQcI GdGOGQI GdhSWi aj GSJQGJjLjI GdHfhc GdYGedI ajgG , JCKjQ GOGQI GdCReGJ Ydi cjajI ehGLgJgG h GdJUOj dgG , CKQ GNdGbjGJ GdGYeGd h GdeSDhdjI GdGLJeGYjI Ydi COGA GdTQcGJ GdeSGgeI GdYGeI GdCQOfjI , GOGQI GdJZjjQ habG dGJLGgGJ GdeOjQjf aj bWGY GdGJUGdGJ GdCQOfj , GdQbGHI GdGOGQjI GdNGQLjI h OhQgG aj JLfH GdGReGJ (B: (3GdJLQHI GdGQOfjI , CSGdjH bjGS h JMdjd GdeNGWQ aj efXeGJ GdCYeGd , JMdjd JWhQ GdGfJGL aj GdefTCI GdUfGYjI GdGQOfjI GdUZjQI NdGd GdaJQI (B2001 (3`` (B2006 (3CKQ GdKbI GdJfXjejI aj bjGS GdCOGA GdGSJQGJjLj HGSJNOGe fehPL HWGbI GdYdGeGJ GdeJhGRfIs
Keywords: (3GOGQI GdGYeGds; (3GdGReGJ GdGbJUGOjIs; (3efXeGJ CUMGH GdYeds